You Are Old, but Are You Out? Intergenerational Contact Impacts on Out-Group Perspective-Taking and on the Roles of Stereotyping and Intergroup Anxiety - Long, Yanxi; Jiang, Xinxin; Wang, Yuqing; Zhou, Xiaoyu; You, Xuqun (Frontiers in Psychology, 2022)
Perspective-taking (PT) is an important ability to imagining the world from another’s vantage point. Previous studies have shown that younger adults are more likely to consider opinions of age-based in-group members relative to out-group members. However, the cause of this priority is still unknown. Based on this gap, we conducted three independent studies to explore the effect of intergenerational contact on younger adults’ perspective-taking toward older adults and the possible roles of stereotype and intergroup anxiety. 192 college students responded in Perspective-Taking scale in Study 1 after priming age-based intergroup relationship and the results indicated that younger adults felt more difficult to take older adults’ perspective than their peers. 200 college students responded Prior Contact scale, Intergroup Anxiety scale, Negative Stereotype scale and Perspective-Taking scale in Study 2, the results demonstrated that intergenerational contact improved perspective-taking toward older adults by disrupting negative stereotypes, and intergroup anxiety moderated this mediation relationship. 215 college students filled Perspective-Taking scale in the context of imagining intergenerational contact in Study 3. Interestingly, imagined contact effectively increased younger adults’ ability to take older adults’ perspectives. The present research verifies that contact is important to influence younger adults’ emotional (intergroup anxiety) and attitudinal (stereotype) factors that are critical to improve younger adults’ ability to take older people’s perspectives, which is of great significance to develop harmonious intergenerational relationships.